1993
DOI: 10.1111/j.1600-0609.1993.tb00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Apparent polycythaemia: diagnosis, pathogenesis and management

Abstract: The term “apparent polycythaemia” is applied to a group of patients who have a raised PCV (<0.51 in males, <0.48 in females) but a normal red cell mass (less than 25% above their predicted mean normal value). Some have additionally a marked reduction in plasma volume and can be defined as a subgroup: relative polycythaemia. Smoking, hypertension and to a lesser extent obesity, excessive alcohol, low‐dose diuretic therapy and hypoxaemia have all been associated with apparent polycythaemia but the mechanism is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…[4][5][6][7][8] Studies comparing monozygotic and dizygotic twins have demonstrated that B50-90% of interindividual variance in WBC, RBC and PLT counts could be attributed to genetic components. 4,5 These heritabilities were observed only within healthy individuals, but genetic factors would also give some variance to disease abnormal data, which may get clinicians confused in interpretation of values.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Studies comparing monozygotic and dizygotic twins have demonstrated that B50-90% of interindividual variance in WBC, RBC and PLT counts could be attributed to genetic components. 4,5 These heritabilities were observed only within healthy individuals, but genetic factors would also give some variance to disease abnormal data, which may get clinicians confused in interpretation of values.…”
Section: Introductionmentioning
confidence: 99%
“…Stress related activation of the sympathetic nervous system has historically been linked with relative polycythemia [8]; in experimental animals, infusion of adrenalin and noradrenaline increases venous tone and causes mild reductions in plasma volume and small increases in PCV [9]. Although the evidence for an association of stress with relative polycythemia is somewhat tenuous [2], we suspect that it played a significant causative role in our patient's polycythemia.…”
Section: Hemoglobin (G/dl)mentioning
confidence: 74%
“…Our patient had four risk factors for Gaisbock's syndrome -hypertension, diuretic therapy, physical and emotional stress, and obesity; of these, hypertension (particularly diastolic hypertension) appears to be the most significant contributor to the polycythemia of Gaisbock's syndrome [2]. In this regard, Emamian and associates studied 9,808 individuals with essential hypertension and found that they had spurious elevations in their hematocrits, hemoglobin levels, red cell counts, and mean corpuscular hemoglobin values [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations